2016
DOI: 10.1021/acs.jmedchem.6b00415
|View full text |Cite
|
Sign up to set email alerts
|

Indole-2-carboxamide-based MmpL3 Inhibitors Show Exceptional Antitubercular Activity in an Animal Model of Tuberculosis Infection

Abstract: Our team had previously identified certain indolecarboxamides that represented a new chemical scaffold that showed promising anti-TB activity at both an in vitro and in vivo level. Based on mutational analysis using bacteria found resistant to one of these indolecarboxamides, we identified the trehalose monomycolate transporter MmpL3 as the likely target of these compounds. In the present work, we now further elaborate on the SAR of these compounds, which has led in turn to the identification of a new analog, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 28 publications
4
144
0
Order By: Relevance
“…The first series is an unsubstituted indole (R = H, compounds 5-19 ) and the second was as 4,6-dimethyl indole (R = CH 3 , compounds 20-34 ). A variety of commercially available bulkyl aliphatic and aromatic head groups were incorporated into final compounds that are consistent with published SAR for previously evaluated urea-based compounds and IC 28, 30, 32-35 .…”
Section: 1 - Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The first series is an unsubstituted indole (R = H, compounds 5-19 ) and the second was as 4,6-dimethyl indole (R = CH 3 , compounds 20-34 ). A variety of commercially available bulkyl aliphatic and aromatic head groups were incorporated into final compounds that are consistent with published SAR for previously evaluated urea-based compounds and IC 28, 30, 32-35 .…”
Section: 1 - Results and Discussionmentioning
confidence: 89%
“…28-32 IC are bioisosteric isomers of published urea based M. tuberculosis inhibitors and have similar structure activity relationships. 33-35 Herein, we report the expansion of i) the chemical space for the published antitubercular IC compounds and ii) the spectrum of antimycobacterial activity.…”
Section: 1 - Introductionmentioning
confidence: 99%
“…tuberculosis and nontuberculous mycobacteria in culture has identified a number of novel chemical entities with potent mycobactericidal activity whose primary target appears to be the essential mycolic acid transporter MmpL3 (14). Among these novel chemical scaffolds, diamine- and indolamide-based compounds have emerged as particularly promising on the basis of efficacy, tolerability, and pharmacological properties (2, 57). The potency of these compounds is owed at least in part to the exquisite vulnerability of the MmpL3 transporter both in vitro and in vivo (1).…”
Section: Textmentioning
confidence: 99%
“…A recent study performed with indolamide inhibitors showed that these compounds synergize with RIF both in vitro and in an acute mouse model of TB infection (2). Likewise, combination studies performed with SQ109, another compound under development whose pleiotropic effects on actively replicating and nonreplicating M.…”
Section: Textmentioning
confidence: 99%
“…Moreover, the in vivo efficacy of this compound was assessed in a mouse infection model and it was able to reduce the bacterial burden on a logarithmic scale of 2.12 log 10 CFU at 100 mg kg −1 dosage level in the lungs after 4 weeks of treatment protecting the mice from death. Altogether, these results pointed out compound ( 38 ) as a promising drug candidate for human clinical trials [64]. …”
Section: Antituberculosis Compoundsmentioning
confidence: 99%